Management of pterygium surgery: Limbal Conjunctival Autograft and Subconjunctival Amniotic Membrane Graft - Reisyah Syahfira; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Pterygium is one of the common ocular surface disorders. From two Greek words, the word